Validation of The Homophobia Scale (HS) Using Rasch Analysis in Indonesia Context - Putri, Alyssa (Jurnal Ilmiah Global Education, 2025)
Homophobia remains a significant social issue, negatively affecting LGBTQ+ individuals and communities. Educational interventions are seen as a promising solution to foster understanding, acceptance, and empathy towards the LGBTQ+ community. This systematic review explores the effectiveness of such interventions in reducing homophobia, drawing from key studies that demonstrate positive impacts. Findings suggest that educational programs can increase knowledge about sexual diversity, promote empathy, and reduce discriminatory behaviors. Despite some limitations, these interventions show potential in creating more inclusive environments, especially when implemented early in educational and community settings. Future research should focus on larger and more diverse samples to strengthen these findings.